PELAKSANAAN JAMINAN SOSIAL KESEHATAN OLEH BADAN PENYELENGGARA JAMINAN SOSIAL KESEHATAN DI RUMAH SAKIT UMUM DAERAH PETALA BUMI PROVINSI RIAU - Mizanty, Novradiella; Hanifah, Mardalena; Hasanah, Ulfia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Social Security Agency of Health is an agency established by the Government which is responsible for providing kesejehteraan people in terms of health. Social Security Agency of Health works on the principle of insurance, namely health insurance are provided to the insured who is already a member and pay dues every month. In this study, the authors are insured, namely the Civil Apparatus Countries using the Social Security Agency facility health at the General Hospital of the Earth Petala Riau Province. Where in the user Apparatus State Civil are getting various constraints, among others, the lack of pengawassan to the insured, the slow pace of service and service are convoluted, so that the insured were less satisfied with the service Regional General Hospital Petala Earth using the facility Social Security Agency of Health,Objectives achieved in writing this essay, among others, to know the process of the implementation of the social security health by the Social Security Agency of Health for the Reform of Civil State in the General Hospital of Petala Earth Riau Province, to determine the existing constraints in providing social security health for Reform of Civil State and efforts that can be done to overcome the existing obstacles in implementing the health insurance for the State Civil Apparatus. This research was socio-juridical, ie research that compares the existing regulations in the legislation applicable to the real conditions on the ground, which will draw conclusions from things that are common to the things that are special.The results of this study describes the implementation, obstacles, and efforts experienced by the Social Security Agency of Health in providing health insurance for the State Civil Apparatus in the General Hospital of the Earth Petala Riau Province. Moreover, I also will give some suggestions that may be useful for future improvements to the various parties involved, namely the State Civil Apparatus, The Social Security Agency of Health and The Regional General Hospital Petala Earth Riau Province.Keywords: Social Security Health, Civil Administrative State, Regional General Hospital Petala Earth Riau Province